1999
DOI: 10.1080/00103629909370251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liming and phosphate application on sudangrass growth and phosphorus availability in two temperate acid soils

Abstract: A pot experiment was carried out in the greenhouse with two loamy sand Dystric Cambisols derived from schist to investigate the effect of liming and phosphorus (P) application on plant growth and P availability and its assessment by four soil test methods: 0.01M calcium chloride (CaCl 2 ), cation anion exchange membrane (CAEM), Egnér-Riehm, and Olsen procedures. Soils were first incubated for two weeks with lime at four levels, depending on their content of exchangeable aluminum (Al). Phosphorus was added at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, these observations could possibly be artefacts of the Olsen method. It has been suggested that Ca and P can precipitate at the increased pH (8.5) of the extract in soils with an abundant supply of Ca, such as limed soils (Sorn‐srivichai et al , 1984; Smith & Sinclair, 1998; Fernandes & Coutinho, 1999). The fact that these results were not reflected by a similar reduction in RP concentrations in soil solution suggests that they may be artefacts of the Olsen method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these observations could possibly be artefacts of the Olsen method. It has been suggested that Ca and P can precipitate at the increased pH (8.5) of the extract in soils with an abundant supply of Ca, such as limed soils (Sorn‐srivichai et al , 1984; Smith & Sinclair, 1998; Fernandes & Coutinho, 1999). The fact that these results were not reflected by a similar reduction in RP concentrations in soil solution suggests that they may be artefacts of the Olsen method.…”
Section: Resultsmentioning
confidence: 99%
“…Liming increases the pH in soil solution. Increased pH leads to increasingly negative charges on soil surfaces, which would tend to decrease sorption of the phosphate anion (Bolan et al , 1988; Fernandes & Coutinho, 1999). However, the composition of the soil’s CEC is also influenced by liming and has a major influence on the pH‐dependence of the P adsorption‐desorption equilibrium (Curtin & Syers, 2001).…”
Section: Effect Of Liming On Phosphorus Solubilitymentioning
confidence: 99%
“…Morton et al (1998) and Fernandes and Coutinho (1999)). Although organic forms of P are not taken up directly by plant root systems, enzyme-labile organic P can be a large soil P pool and an important source of P for plants (Asmar et al 1995;George et al 2002;Hayes et al 2000;McDowell and Koopmans 2006;Shand and Smith 1997).…”
Section: Organic Phosphorusmentioning
confidence: 94%
“…The overall effect of lime on RP solubility may depend on several competing effects of raised pH and Ca concentration that vary between soils. Generally, as pH increases, negative charges on soil surfaces also increase, leading to desorption of the phosphate anion (Bolan et al 1988;Fernandes and Coutinho 1999). Soils 1 and 2 had the largest increases in pH with liming (1.7 and 0.5, respectively), so phosphate desorption may have been responsible for increasing RP solubility in these soils.…”
Section: Reactive Phosphorusmentioning
confidence: 96%
“…The application of lime did not show a significant increase in M3 extractable P concentration in the current study, despite the large reduction in Al and Fe concentration. Increasing soil pH resulted in increased base saturation on the soil surface, thus reducing the sorption of P anions (Fernandes and Coutinho, 1999) and increasing plant available P (Ortas and Rowell, 2000).…”
Section: Lime Applicationmentioning
confidence: 99%